Réponses

2013-05-24T22:10:37+02:00

1) Je factorise:

 

D= (x-2)² -2(x-2) 

= (x-2)(x-2) -2(x-2)

= (x-2)(x-2-2)

=(x-2)(x-4)

 

 

2) Je développe:

 

D= (x-2)² -2(x-2) 

= (x-2)(x-2) -2(x-2)

= x²-2x-2x +4 -2x +4

= x² -6x +8

 

3) D pour x=1:

 

 

x² -6 +8

= 1² -6+8

= 1-6+8

= 3

 

 

 

En espérant ne pas mettre trompée dans les calculs!

 

 

 

 

2013-05-24T22:17:38+02:00
1). (x-2)[(x-2)-2]

2). (x-2)(x-2) -(2x-4)
= x^ -2x -2x + 4 -2x +4
= x^ -6x + 8

3). Pour x= 1
(1-2)^ -2(1-2)
= (-1)^ -2+4
= 1-2 +4
= 3